Leupaxin Expression Is Dispensable for B Cell Immune Responses - Bonaud, Amélie; Clare, Simon; Bisio, Valeria; Sowerby, John M.; Yao, Shugang; Ostergaard, Hanne; Balabanian, Karl; Smith, Kenneth G. C.; Espéli, Marion (Frontiers in Immunology, 2020)
The generation of a potent humoral immune response relies on the integration of signals by B cells induced by the B cell receptor, toll-like receptors and both negative and positive co-receptors. Several reports also suggest that integrin signalling plays an important role in this process. How integrin signalling is regulated in B cells is however still partially understood. Integrin activity and function are controlled by several mechanisms including regulation by molecular adaptors of the paxillin family. In B cells, Leupaxin (Lpxn) is the most expressed member of the family and in vitro studies suggest that it could dampens BCR signalling. Here, we report that Lpxn expression is increased in germinal centre B cells compared to naïve B cells. Moreover, Lpxn deficiency leads to decreased B cell differentiation into plasma cells in vitro. However, Lpxn seems dispensable for the generation of a potent B cell immune response in vivo. Altogether our results suggest that Lpxn is dispensable for T-dependent and T-independent B cell immune responses.